Effect of Adrenaline on Thrombosthenin - Levy-Toledano, S; Caen, J; with the technical assistance of Eva Bodevin (Thrombosis and Haemostasis, 1971)
It has been found that adrenaline protects the two activities of thrombosthenin from inhibition by NEM if added before or with NEM but not if added after.The α-blockers of epinephrine, phentolamine, abolishes the protective effect of adrenaline when it is added before adrenaline. We find the same results with noradrenaline but not with 5-hydroxytryptamine.A parallemism exists between the effect of adrenaline on thrombosthenin and clot retraction, but not on platelet aggregation. This shows possibly that the activities of thrombosthenin are directly linked to clot retraction, but in platelet aggregation it seems that thrombosthenin is necessary but not sufficient.